HUBUNGAN PENDIDIKAN DENGAN KEPERCAYAAN DIRI IBU DALAM MERAWAT BAYI PREMATUR DI RSAB HARAPAN KITA JAKARTA BARAT TAHUN 2023 - Fathia Nurfadillah Aninda (2023)
This research is motivated by the high number of cases of premature birth in 2014-2015, Indonesia is one of the countries that contributes the highest premature rates, namely 19% and is a major factor in perinatal death. Harapan Kita Hospital, West Jakarta, has a rate of 3.46%, around 105 mothers who gave birth to premature babies within 3 months. The formulation of this problem is the health of premature babies who need intensive and special care so that most of them can affect the confidence of the baby's parents. The purpose of this study was to find out whether there is a relationship between mother's education and mother's confidence in caring for premature babies at Harapan Kita Hospital, West Jakarta. This study used a quantitative method and used a cross sectional approach with 38 samples obtained by non-probability sampling method and total sampling technique. The results showed that there was no significant relationship between mother's education and mother's confidence in caring for premature babies with a p-value of 0,721 (≥ 0.05). Keyword : Premature birth, Confidence, Education